Pengukuran Modulus Elastisitas Dinamis Batuan dengan Metode Seismik Refraksi - Ashadi Salim (Bina Nusantara University, 2012)
The seismic wave velocity in rock formation depends on the elastic modulus and mass density of rock where the wave travels. The velocity measurement of P and S waves on rock formation and the mass density in the laboratory can be used for calculating the elastic modulus of rock formation. The elastic modulus is part of rock mechanical parameter needed in geological engineering researches. The velocity measurement of P and S waves by the seismic refraction method was done on a tunnel with 11 spreads of measurement. From the results of the measurement, three groups of rock formation could be identified. The first is rock formation with Ed=8.890-12.68 MPa and G=3.306-4.830MPa; the second group is rock formation with Ed=8.890-12.68 MPa and G=3.306-4.830MPa; and the third group is with Ed=18.520-21.120MPa and G=6.724-7.744MP. The first group is clay formation while the second and third groups are andesitic stone formation.